Recent progress in serine metabolism reprogramming in tumors and strategies for serine deprivation - Liu, Huimei; Liu, Yanping (Frontiers in Oncology, 2025)
Tumor cells undergo extensive metabolic reprogramming during malignant proliferation, with serine—a key nonessential amino acid—playing multiple roles in tumor metabolism. To maintain high serine levels, tumor cells upregulate phosphoglycerate dehydrogenase to enhance endogenous synthesis and concurrently increase exogenous uptake. Serine deprivation demonstrates antitumor potential across various malignancies; however, its clinical application remains limited by inadequate tumor selectivity and systemic toxicity. Recent advances in nanodelivery systems offer precise strategies to modulate tumor serine metabolism. Serine deprivation via these systems improves tumor-specific targeting while minimizing off-target toxicity to normal tissues. Therefore, this review aims to outline serine metabolism and its regulatory networks, evaluate the therapeutic potential and limitations of serine deprivation, and highlight recent advances in nanodelivery strategies targeting serine metabolism for cancer therapy, thereby providing insights for the development of novel anticancer approaches.